Sodium iodide symporter-targeted gene therapy in glioblastoma - Nicola, Juan Pablo (2023)
Sodium iodide symporter (NIS) gene transfer for active accumulation of radioactive iodide (or alternative radionuclides) in tumor cells is a powerful theranostic strategy allowing for both diagnostic and therapeutic applications. In the current issue of Molecular Therapy – Oncolytics, Spellerberg et al.1 designed NIS plasmid DNA polyplexes containing targeting ligands for the transferrin receptor (TfR) and the epidermal growth factor receptor (EGFR) in order to improve active transport across the blood-brain barrier, followed by targeting of glioblastoma cancer cells, an aggressive and therapeutically challenging brain tumor.